Method for evaluation of ionic interactions in liquid chromatography - Kadlecová, Zuzana; Kalíková, Květa; Folprechtová, Denisa; Tesařová, Eva; Gilar, Martin (Journal of chromatography. A, Including electrophoresis and other separation methods, 2020)
In this work we utilized basic and acidic analytes to investigate the ionic interaction participation in retention behavior of selected reversed-phase and polar columns. The test analytes included nitrate, benzenesulfonate and trimethylphenylammonium ions. The fully aqueous mobile phase comprising 10 mM dichloroacetic acid buffered with ammonia solution to desirable pH was used for retention experiments. Developed method was utilized to study the ionic interactions of stationary phases in pH range between 2.5 and 9.0. We demonstrate that selected sorbents used for reversed-phase and hydrophilic interaction chromatography separations exhibit cation- or anion-exchange interactions. We compare the results to novel Atlantis PREMIER BEH C18 AX mixed-mode column that combines reversed-phase and anion-exchange interaction modes. We evaluated the relative retention strength of selected columns for anionic and cationic analytes.
Keywords: oxid křemičitý; Adsorption; voda; anionty; Silicon Dioxide; Water; Anions; Chromatography, Reverse-Phase; Chromatography, Liquid; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; chromatografie s reverzní fází; hydrofobní a hydrofilní interakce; chromatografie kapalinová; adsorpce; Hydrophobic and Hydrophilic Interactions